A Deletion at the Mouse Xist Gene Exposes Trans-effects That Alter the Heterochromatin of the Inactive X Chromosome and the Replication Time and DNA Stability of Both X Chromosomes - Diaz-Perez, Silvia V. (Copyright © 2006 by the Genetics Society of America, 2006)
The inactive X chromosome of female mammals displays several properties of heterochromatin including late replication, histone H4 hypoacetylation, histone H3 hypomethylation at lysine-4, and methylated CpG islands. We show that cre-Lox-mediated excision of 21 kb from both Xist alleles in female mouse fibroblasts led to the appearance of two histone modifications throughout the inactive X chromosome usually associated with euchromatin: histone H4 acetylation and histone H3 lysine-4 methylation. Despite these euchromatic properties, the inactive X chromosome was replicated even later in S phase than in wild-type female cells. Homozygosity for the deletion also caused regions of the active X chromosome that are associated with very high concentrations of LINE-1 elements to be replicated very late in S phase. Extreme late replication is a property of fragile sites and the 21-kb deletions destabilized the DNA of both X chromosomes, leading to deletions and translocations. This was accompanied by the phosphorylation of p53 at serine-15, an event that occurs in response to DNA damage, and the accumulation of γ-H2AX, a histone involved in DNA repair, on the X chromosome. The Xist locus therefore maintains the DNA stability of both X chromosomes.